Behaviour of ink droplet media interactions in model systems - Bucknall, A; Dupuis, A; Leopoldes, J; Wilkins, S; Yeomans, J; Is, T (2003)
In this work we present a study of the characteristics of UV cure ink droplets on different media (model homogeneous and heterogeneous surfaces, PET, treated PET, etc.). By varying the magnitude of chemical heterogeneities on model surfaces, we are able to highlight the parameters that affect droplet shape. Using Lattice Boltzmann simulations of droplet spreading, we show that the location of the impact point of a droplet on patterned substrate with micron size chemical heterogeneity is an important criterion to consider with respect to the equilibrium shape of a droplet. This allows a complete understanding of the effect of chemical heterogeneity on droplet shape, and therefore on printing quality. We also report an experimental study of the morphology of ink droplets adsorbed on chemically defined substrates. This morphology appears to be related with the surface properties of the media considered.